High-frequency stimulation of the subthalamic nucleus counteracts cortical expression of major histocompatibility complex genes in a rat model of Parkinson’s disease - Grieb, Benjamin; Papageorgiou, Ismini E. (PLOS ONE, 2014)
High-frequency stimulation of the subthalamic nucleus (STN-HFS) is widely used as therapeutic intervention in patients suffering from advanced Parkinson’s disease. STN-HFS exerts a powerful modulatory effect on cortical motor control by orthodromic modulation of basal ganglia outflow and via antidromic activation of corticofugal fibers. However, STN-HFS-induced changes of the sensorimotor cortex are hitherto unexplored. To address this question at a genomic level, we performed mRNA expression analyses using Affymetrix microarray gene chips and real-time RT-PCR in sensorimotor cortex of parkinsonian and control rats following STN-HFS. Experimental parkinsonism was induced in Brown Norway rats by bilateral nigral injections of 6-hydroxydopamine and was assessed histologically, behaviorally, and electrophysiologically. We applied prolonged (23h) unilateral STN-HFS in awake and freely moving animals, with the non-stimulated hemisphere serving as an internal control for gene expression analyses. Gene enrichment analysis revealed strongest regulation in major histocompatibility complex (MHC) related genes. STN-HFS led to a cortical downregulation of several MHC class II (RT1-Da, Db1, Ba, and Cd74) and MHC class I (RT1CE) encoding genes. The same set of genes showed increased expression levels in a comparison addressing the effect of 6-hydroxydopamine lesioning. Hence, our data suggest the possible association of altered microglial activity and synaptic transmission by STN-HFS within the sensorimotor cortex of 6-hydroxydopamine treated rats.